Sustainable Tourism in Thailand: A Scoping Review - Sansri, Rakpong; Vorasingha, Tanawan (Journal of Humanities and Social Sciences Thonburi University, 2024)
The purpose of this research was to conduct a scoping review of sustainable tourism in the context of Thailand and provide recommendations about developing the research and policy on sustainable tourism in Thailand. Qualitative method research through scoping review was adopted. Article selection was made based on the PRISMA Extension for Scoping Reviews (PRISMA-ScR). Data extraction tool was also used. The findings revealed that 51 articles were eligible for conducting scoping review. The southern region of Thailand had been heavily investigated under sustainable tourism in Thailand. Sustainable tourism development was a mostly examined theme in those studies. For the breadth of variables, there have been 29 variables employed in the quantitative method research while qualitative approach has investigated 12 issues. Recommendations about future research and policy on sustainable tourism in Thailand are as the following. The stakeholders in the Thai tourism industry are highly recommended to adopt the GSTC Criteria into their tourism-related activities. Based on the research gap, future research is recommended to examine the effects of sustainable tourism on the stakeholders of tourism industry, effects of sustainable tourism on a reduction of income gap between urban and rural areas, and revisitation of sustainable tourism destinations.